Pengaruh Media Sosial Terhadap Moral dan Etika dalam Perspektif: Sila Kedua - Eka Putriani Sihombing; Yakobus Ndona (Lembaga Pengembangan Kinerja Dosen, 2024)
Social media has become an important communication and information transfer platform in the current era of digitalization. Despite providing many great benefits in terms of relationships and access to information, the unethical use of communicative language and lack of understanding of ethical values ​​on social media has created a significant ethical crisis. This research aims to analyze the influence of social media on morals and ethics in the appreciation of human values. This research method uses the library research method, namely by collecting data or scientific papers which are intended as research objects by collecting data of a library nature. The data collection technique used is literature data collection relating to the influence of social media on morals and ethics in the appreciation of human values. The data obtained can be used to find out and improve people's morals and ethics in using social media to be wiser. The analysis was carried out descriptively qualitatively, namely by describing systematically, in detail and comprehensively the influence of social media on ethics and morals in the appreciation of human values ​​which has an impact on the decline in human values ​​such as empathy, mindfulness and attention to other people.